2018
DOI: 10.1007/s12221-018-7210-z
|View full text |Cite
|
Sign up to set email alerts
|

Unprecedented Electromagnetic Shielding Effectiveness of Lightweight Nonwoven Ag/PA66 Fabrics

Abstract: Novel, high-performance silver coated polyamide, Ag/PA66, nonwoven fabrics with a density of only 0.04g/cm 3 have been developed using staple fibres of 19 (3.3dtex) and 27 (6.7dtex) μm diameter.The obtained nonwoven fabrics with an Ag loading of 12-18wt% exhibited excellent weight-normalised specific electromagnetic shielding effectiveness of over 1200 dB/(g/cm 3 ) in the 0.015-3GHz range, which is among the highest reported till date. Moreover, the applied microwave was verified to be absorbed rather than bei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…M.S. Ozenet et al [6] reported that the shielding effect of nonwoven made of 6.7 dtex and 3.3 dtex conductive Ag/PA66 staple fibers was about 69–80 dB when the weight of nonwoven was only 0.04 g/cm 2 .…”
Section: Introductionmentioning
confidence: 99%
“…M.S. Ozenet et al [6] reported that the shielding effect of nonwoven made of 6.7 dtex and 3.3 dtex conductive Ag/PA66 staple fibers was about 69–80 dB when the weight of nonwoven was only 0.04 g/cm 2 .…”
Section: Introductionmentioning
confidence: 99%
“…where t is the thickness of the shielding materials (mm), f is the incident wave frequency (MHz), is skin depth, and r and r are the conductivity and permeability relative to Cu, respectively. The increase of r and r due to increased SS fiber content in yarn resulted in better R and A values according to equations (2) and (3), which further led to the increase of SE values according to equation (1). That's why fabrics containing 30% SS fibers show the higher ability of EMSE than fabrics with 25% SS fibers content.…”
Section: Effect Of Ss Fiber Content On Emse and Mechanism Analysismentioning
confidence: 93%
“…With the development of electronic industry, people's life is flooded with a large number of electromagnetic waves, which endangers human health and interferes with the operation of electronic equipment, thus leading to the increasing demand for radiation-proof functional textiles. Recent research papers on electromagnetic shielding effectiveness (EMSE) mainly focus on technology of electromagnetic shielding (EMS) materials [1][2][3][4][5], influencing factors [6][7][8][9][10][11][12], or calculation [12][13][14][15][16]. The blended metal fabric-EMS has so many advantages in price, technology maturity, EMS performance, and wear ability that it has become one of the most widely used EMS fabrics [7].…”
Section: Introductionmentioning
confidence: 99%
“…Electromagnetic radiation not only adversely affects human health and the environment, but also causes interference to electronic equipment and even causes major information losses. Therefore, electromagnetic shielding has received increasing attention, shielding materials play an important role in shielding effects, and the research on shielding materials becomes urgent [1][2][3].…”
Section: Introductionmentioning
confidence: 99%